Pulmonary mixed squamous cell and glandular papilloma clinicopathological characteristics of 2 cases and misdiagnosis analysis of frozen section - CHE Wen, LIU Jiangshu, CHEN Xiaoyan, WANG Chaofu, YUAN Fei, WANG Xuan (Zhenduanxue lilun yu shijian, 2022)
Objective: To discuss the clinicopathologic characteristics of pulmonary mixed squamous cell and glandular papilloma(PMSGP), and to analyze the key points for diagnosis and the causes of misdiagnosis of frozen section. Methods: Two cases of PMSGP diagnosed by pathology at Ruijin Hospital, Shanghai Jiao Tong University School of Medicine from 2019 to 2021 were enrolled, and the clinicopathologic and immunohistochemical characteristics and key points of frozen section diagnosis were analyzed based on literature review. Results: Two patients, a 74-year-old female and a 66-year-old male, were found to have pulmonary nodules in physical examination. One patient had chest tightness and pain. All nodules were considered as malignant tumors on imaging and lobectomy was performed. Frozen sections indicated one case was diagnosed as mucinous adenocarcinoma and the other diagnosed as PMSGP, but mucoepidermoid carcinoma could not be ruled out. In the paraffin section, the tumor sizes of 2 cases were 3.0 cm×2.5 cm×2.5 cm and 1.7 cm×1.7 cm×1.6 cm respectively. PMSGP displayed a papillary growth pattern lined by glandular epithelial cells and squamous cells. Inflammatory cells were observed along the papillary axis. Squamous epithelium could be mild to moderately atypical with rare mitosis and no necrosis. Immunohistochemistry examination showed that CK7 and TTF-1 were expressed in glandular epithelial cells, MUC5AC was expressed in mucinous columnar epithelial cells, squamous cells and basal-like cells expressed CK5/6, P63, P40 and Ki-67 was highly expressed only in the basal layer. MAML2 rearrangement was not detected in the 2 cases by FISH. No recurrence or metastasis was observed at 9 and 24 months of follow-up. A literature review of 39 cases showed that due to the morphological crossover with mucoepidermoid carcinoma and mucinous adenocarcinoma, and the atypical nature of the covered squamous epithelium was easily amplified in frozen section diagnosis, the misdiagnosis rate of PMSGP of tumor properties on frozen section is as high as 52.6%. Conclusions: PMSGP is a rare benign tumor of the lung, that has a high rate of misdiagnosis on frozen section. On frozen section, the tumor is well defined and has a papillary structure. The papilla is covered with squamous epithelium and glandular epithelium. Basal cells are arranged in a palisade pattern along the fibrovascular axis, and the cells are stratified without atypia. Mastering these characteristics helps to improve the diagnostic accuracy of frozen section.